Analisis Wirausaha pariwisata Santerra De Laponte Kecamatan Pujon, Kabupaten Malang, Jawa Timur - Puspitasari Puspitasari; Melati Afriani; Sela Mitha; Risma Risma; Nuraisyah Nuraisyah; Syarif Permana Salingkat; Gita Farista (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
Entrepreneurship is a creative and innovative ability, keen to see opportunities and always open to every input and positive change that can lead to continued business growth. Entrepreneurship is also a dynamic process to create added value for goods and services and prosperity. Tourism is one of the potential sectors that can be developed by regions to build an area with the help of the government, community, and private sector. The type of this research is field research which is a method to find specifically and realities related to what is happening in the midst of a community. This field research generally aims to solve practical problems in everyday life. The results of this study indicate that Santerra de Laponte Tourism is located in a strategic location that is easily accessible to tourists from various regions. The existence of this tourist area is expected to have a positive impact on the local economy through increased tourist visits, job creation, and increased income for the surrounding community. Santerra de Laponte Tourism has a significant positive impact on the local economy through increased tourist visits.